Effect of Stress on High-Temperature Molten Salt Corrosion of T91 Steel - Kai Yan; Bingjie Shi; Shaohai Ma; Peihan Li; Zhongliang Zhu (Metals)
This paper reports the effects of different levels of tensile stress caused by quasi-static loading on the corrosion behavior of T91 steel in a molten salt environment. Corrosion tests were carried out in a molten salt environment with a NaCl:K2SO4:Na2SO4 ratio of 1:1:8 under different applied stresses. The corrosion behavior was investigated through measurements of the phase composition, oxide morphology, and elementary composition. The results indicated that a low tensile stress promotes the growth of chromium oxides near the substrate and enhances the corrosion resistance, but with an increase in stress, the chromium oxides that formed on the T91 steel are destroyed, accelerating the inward diffusion of sulfur into the substrate to increase corrosion. The mechanism underlying the effects of applied stress and temperature on the corrosion behavior of T91 steel is discussed.